Molecular and morphological data support the existence of a sexual cycle in species of the genus Paracoccidioides - Teixeira, Marcus de Melo; Theodoro, Raquel Cordeiro [UNESP]; Derengowski, Lorena da Silveira; Nicola, André Moraes; Bagagli, Eduardo [UNESP]; Felipe, Maria Sueli (American Society for Microbiology, 2013)
The genus Paracoccidioides includes the thermodimorphic species Paracoccidioides brasiliensis and P. lutzii, both of which are etiologic agents of paracoccidioidomycosis, a systemic mycosis that affects humans in Latin America. Despite the common occurrence of a sexual stage among closely related fungi, this has not been observed with Paracoccidioides species, which have thus been considered asexual. Molecular evolutionary studies revealed recombination events within isolated populations of the genus Paracoccidioides, suggesting the possible existence of a sexual cycle. Comparative genomic analysis of all dimorphic fungi and Saccharomyces cerevisiae demonstrated the presence of conserved genes involved in sexual reproduction, including those encoding mating regulators such as MAT, pheromone receptors, pheromone-processing enzymes, and mating signaling regulators. The expression of sex-related genes in the yeast and mycelial phases of both Paracoccidioides species was also detected by realtime PCR, with nearly all of these genes being expressed preferentially in the filamentous form of the pathogens. In addition, the expression of sex-related genes was responsive to the putative presence of pheromone in the supernatants obtained from previous cocultures of strains of two different mating types. In vitro crossing of isolates of different mating types, discriminated by phylogenetic analysis of the α-box (MAT1-1) and the high-mobility-group (HMG) domain (MAT1-2), led to the identification of the formation of young ascocarps with constricted coiled hyphae related to the initial stage of mating. These genomic and morphological analyses strongly support the existence of a sexual cycle in species of the genus Paracoccidioides. © 2013, American Society for Microbiology.
Keywords: mating hormone alpha factor receptor; sex pheromone; asexual reproduction; chemistry; cytology; fungal gene; fungal genome; fungus hyphae; fungus spore; genetic transcription; genetics; high mobility group box domain; metabolism; Paracoccidioides; phylogeny; physiology; Saccharomyces cerevisiae; sequence homology; Genes, Mating Type, Fungal; Genome, Fungal; HMG-Box Domains; Hyphae; Phylogeny; Receptors, Mating Factor; Reproduction, Asexual; Sequence Homology; Sex Attractants; Spores, Fungal; Transcription, Genetic